Arrhythmic Mitral Valve Prolapse with Features of Mitral Annular Disjunction and Myocardial Tissue Changes as Assessed with Cardiac Magnetic Resonance - Sahara, Elen; Wicaksono, Swandito; Atmadikoesoemah, Celly (Jurnal Kardiologi Indonesia, 2024)
Background. Mitral valve prolapse (MVP) is a rare disorder linked to abrupt cardiac mortality and malignant ventricular arrhythmias. Beyond conventional prognostic indicators, risk stratification may have a promising function in MVP patients, as cardiac magnetic resonance imaging (CMR) can identify tissue alterations in these patients. Case Illustration. A 36-year-old female with palpitation, dyspnea on effort, and episode of near syncope had multifocal premature ventricular complex (PVC) with right bundle branch block patern. Bileaflet MVP with multifocal benign infrequent PVC from posteromedial papillary muscle was diagnosed in this patient based on echocardiography and holter monitoring. Mitral annular disjuction (MAD), mitral regurgitation (MR), tricuspid regurgitation (TR) were also noticed. CMR examination confirmed moderate MR ec AML-PML prolapse with MAD at PML (P1, P2, P3), moderate TR ec anterior tricuspid leaflet prolapse, myocardial inflammation and myocardial fibrosis. Conclusion. We present case report of a young woman diagnosed with PVC predominant from posteromedial papillary muscle and bileaflet with features of MAD, myocardial inflammation and fibrosis. The arrhythmogenesis in MVP involves the development of a substrate for arrhythmias combined with a trigger for arrhythmias. Future prospective research is needed to further delineate optimal methods for risk stratification and treatment